In vitro antitumoral effects of the combination of Curcuma longa and prednisolone on inhibition of the NF-κB signaling pathway - Dehghan-Nayeri, Nasrin; Bahmani, Forouzan; Gharehbaghian, Ahmad (Archives of Advances in Biosciences, 2017)
Acute lymphoblastic leukemia (ALL) is the most common cancer among children. Despite recent treatment advances, about 80 percent of patients indicate resistance to treatment and the relapse remains a significant clinical problem. Apoptotic-resistant leukemia cells exhibit an unusual response to the NF-κB pathway; therefore, inhibiting this pathway can sensitize resistant cells to treatment. IKK-NF-kappaB signaling is an important factor in carciogenesis and a potential target for cancer treatment. Therefore, in this study, the mRNA expression of targets of NF-κB signaling including IKKalpha, IKKbeta and also NF-κB were analyzed, using the real time-PCR in the face of the combined effect of Curcuma longa and prednisolone in the ALL cell line of NALM-6. Results of the study showed significant downregulation of three genes after combination Curcuma longa (5 µg/ml) and prednisolone (1 μM) in comparison with the single agents alone. These findings unveiled the synergistic effect of Curcuma longa and prednisolone on IKKα and IKKβ downregulation and NF-κB inhibition that can be considered as a new approach in the ALL treatment of resistance to chemotherapy.